Condicionamento neotectônico na rede de drenagem e no relevo do baixo curso do Rio Doce (Espírito Santo, Sudeste do Brasil) - Busato, Cirla (2020)
This research had as general objective to investigate the relationship between the relief and the drainage network with neotectonic mechanisms in the low course of the Doce River (Espírito Santo - southeastern Brazil). The methodological basis used was part of the cabinet and field analyzes. The cabinet analyzes were carried out in 3 (three) stages: i) bibliographic review on the research topic; ii) elaboration of maps; iii) interpretation of aerial photographs (Digital Orthophoto). In the field, the main drainage anomalies, morphotectonic features and lithology of the geological compartments were verified, all registered with a camera with a resolution of 10.1 megapixels and GPS (Global Position System). Based on the analysis of the drainage network and the morphotectonic features in the cabinet and in the field, two strongly contrasting compartments can be identified, directly related to the basic geological subdivision of the state of Espírito Santo: i) Precambrian Basement Compartment, to the west of the studied area and ii) Cenozoic Deposit Compartment, east of the studied area. From the analysis of the lineaments, the drainage network, the relief, the morphotectonic and neotectonic features, in the cabinet and field stages, it was possible to identify several physiographic elements that show probable neotectonic controls, with the following being particularly notable: drainage network where the river channels are geometrically organized, straight and barred barred lakes, drainage anomalies, tectonically controlled drainage patterns, identification of tectonic blocks through the analysis of the Base Surface Map. In addition, some morphotectonic features have been identified, such as fault cliff, linear cliff, sedimentation wells, asymmetric valley, rectilinear valley. It was observed that the guidelines NNW-SSE and NW-SE of the lineaments, and the orientations of the structural trends predominate in the Compartments of the Precambrian Basement and of the Sedimentary Deposits. The NNE-SSW and NE-SW orientations are secondarily important in the two geological compartments of the basin. The NNESSW orientation of the drainage network predominates in the Precambrian Basement Compartment. However, in the Cenozoic Sedimentary Deposit Compartment, these guidelines can be directly attributed to Neotectonic billing standards. In addition, there was a continuity of structural trends, present in the density map of lineaments that extend from sedimentary rocks to basement rocks, with the same orientation, being able to document neotectonic reactivations. After the characterization of the main guidelines of the lineaments, structural trends and drainage network, and the relationship of these data with the data of neotectonic failures described for the area, present in the literature, it was observed that the studied area fits into the regimes neotectonics recognized for the state of Espírito Santo: i) sinister EW occurrence, attributed to a neogenic age; ii) dextral EW occurrence, considered to be of Pleistocene to Holocene age; and iii) NW-SE distension, of Holocene age, also recognized in other studies in southeastern Brazil and which has a strong Neotectonic control, attested in all the products elaborated and confirmed at work field.